CNSC-08. TUMOUR-INFILTRATED CORTEX PARTICIPATES IN LARGE-SCALE COGNITIVE CIRCUITS. (14th November 2022) - Mandal, Ayan; Assem, Moataz; Romero-Garcia, Rafael; Coelho, Pedro; McDonald, Alexa; Woodberry, Emma; Morris, Robert; Price, Stephen; Duncan, John; Santarius, Thomas; Suckling, John; Hart, Michael; et al.
Abstract: In neurosurgery, tumour-infiltrated cortex is generally assumed to be non-functional. While prior studies have suggested integration of tumour-infiltrated tissue in relatively local circuits responsible for language and motor function, it is unknown whether such tissue can participate in distributed networks important for higher-order cognitive abilities like executive function. We tested the hypothesis that diffuse low-grade gliomas integrate into large-scale cognitive circuits using intracranial electrocorticography and resting-state functional magnetic resonance imaging of four patients. To identify brain areas recruited for executive function, electrocorticography recordings were acquired from tumour-infiltrated tissue under three conditions: i) baseline (rest), ii) simple counting (1-20; "easy"), and iii) switch counting (1-a-2-b-3-c etc.; "hard"). In each patient, we observed significant task-based high gamma power modulations in tumour-infiltrated cortex in response to increasing cognitive effort ( p < 0.05), implying preserved functionality of neoplastic tissue for complex tasks. Additionally, tumour locations corresponding to task-responsive electrodes exhibited functional connectivity patterns that significantly co-localised with canonical brain networks implicated in higher-order cognitive processing ( p < 0.05). Finally, dorsal attention network connectivity in tumour-infiltrated cortex correlated with high gamma power elevations during increased cognitive demand (χ  2 (1) = 5.14; p = 0.023), establishing a concordance between both techniques. Overall, this study contributes convergent evidence that tumour-infiltrated cortex can participate in large-scale neurocognitive circuits, prompting a reconsideration of traditional notions of neoplastic brain tissue.